Social Emotional Learning in Schools: The Importance of Educator Competence. (March 2023) - Gimbert, Belinda G.; Miller, Dustin; Herman, Emily; Breedlove, Meghan; Molina, Citlali Estela
As professionals charged with fostering student learning and well-being, educators—school leaders, teachers, school counselors, pre-service teachers—should demonstrate social emotional competence. In this study, we apply the Collaborative for Academic, Social, and Emotional Learning's framework—self-awareness, self-management, social awareness, relationship skills, responsible decision-making—to ascertain what we know from scholarship about educators' SEL competence. We conclude with guiding principles for training programs and professional learning opportunities for strengthening educators' understanding of their own SEL to improve daily pedagogical practice and ensure each school-wide initiative around SEL drives seamless strategies for attaining school improvement outcomes.